Routing in mobile ad hoc networks with periodic broadcasts - Li, Geng Zhen. (2010)
Future wireless applications will take advantage of rapidly deployable and self-configuring ad hoc networks. Many ad hoc networks utilize hello message to determine local connectivity. The factors that influence the utility of hello messages based on Ad hoc On-Demand Distance Vector (AODV) were investigated by many researchers. In this project, an analysis of the two existing problems of AODV in mobile ad hoc networks is presented and a new mechanism is proposed. We present an improved scheme called traffic-aware beacon which is based on original AODV for dynamic traffic environment. This modified protocol analyzes different network traffic and then adapts the broadcasting frequency of hello messages. In additional, the transmission rate can be increased when the channels between neighbors are in a light traffic. Compared with the original AODV in the same scenario, the modified AODV achieves better performance in terms of packet throughput (CBR model) as well as packet drop ratio (VBR model).